Migration Histories of the Medieval Afroeurasian Transition Zone Aspects of mobility between Africa, Asia and Europe, 300-1500 C.E. - Preiser-Kapeller, Johannes; Reinfandt, Lucian; Stouraitis, Yannis (Studies in Global Social History, 2020)
This volume offers a systematic survey of migration histories in the central transition zone between Africa, Asia and Europe from the 4th to the 15th century C.E.; Readership: All interested in the medieval history of the regions between the Mediterranean and Central Asia and between Eastern Europe and the Indian Ocean and phenomena of migration and human mobility.